Effect of HSV-2 Suppressive Therapy on Genital Tract HIV-1 RNA Shedding among Women on HAART: A Pilot Randomized Controlled Trial - A. E. Nijhawan; A. K. DeLong; S. Chapman; A. Rana; J. Kurpewski; J. Ingersoll; A. M. Caliendo; S. Cu-Uvin (Hindawi Limited, 2012)
Background. The role of suppressive HSV therapy in women coinfected with HSV-2 and HIV-1 taking highly active antiretroviral therapy (HAART) is unclear. Methods. 60 women with HIV-1/HSV-2 coinfection on HAART with plasma HIV-1 viral load (PVL) ≤75 copies/mL were randomized to receive acyclovir (N=30) or no acyclovir (N=30). PVL, genital tract (GT) HIV-1, and GT HSV were measured every 4 weeks for one year. Results. Detection of GT HIV-1 was not significantly different in the two arms (OR 1.23, P=0.67), although this pilot study was underpowered to detect this difference. When PVL was undetectable, the odds of detecting GT HIV were 0.4 times smaller in the acyclovir arm than in the control arm, though this was not statistically significant (P=0.07). The odds of detecting GT HSV DNA in women receiving acyclovir were significantly lower than in women in the control group, OR 0.38, P<0.05. Conclusions. Chronic suppressive therapy with acyclovir in HIV-1/HSV-2-positive women on HAART significantly reduces asymptomatic GT HSV shedding, though not GT HIV shedding or PVL. PVL was strongly associated with GT HIV shedding, reinforcing the importance of HAART in decreasing HIV sexual transmission.